IMPROVEMENT OF METHODOLOGICAL COMPETENCES OF FUTURE ENGLISH LANGUAGE TEACHERS IN THE CONDITIONS OF IMPLEMENTATION OF INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Bozorova Lobar Bazarbayevna (American Journals, 2024)
The purpose of this article is to look into how teachers prepare for and use multimedia when instructing English language learners. Two English teachers served as the research subjects in this case study methodology study. According to the findings, teachers obtain their preparation materials from a variety of sources, including the internet, books, and videos. The devices' limitations presented a challenge for the teachers. When putting an activity into practice, the teacher frequently used films, followed by power point presentations to clarify the content. Teachers hardly ever administer assessments that require students to use multimedia. This article offers ideas and viewpoints on enhancing future English language instructors' methodological proficiency in the context of implementing cutting-edge.
Keywords: English, multimedia, innovative technologies, educational process, preparation, implementation,students, media tools, methodological competencies, improvements.